Lesion enhancement in radio-frequency spoiled gradient-echo imaging: theory, experimental evaluation, and clinical implications. - Rand, S; Maravilla, K R; Schmiedl, U (American Journal of Neuroradiology, 1994)
PURPOSE To investigate the lesser lesion conspicuity after gadolinium contrast infusion with radio-frequency spoiled gradient-echo (SPGR) sequences relative to conventional T1-weighted spin-echo techniques. METHODS The influences of repetition time, echo time, and flip angle on spin-echo and SPGR signal were studied with mathematical modeling of the image signal amplitude for concentrations of gadopentetate dimeglumine solute from 0 to 10 mM. Predictions of signal strength were verified in vitro by imaging of a doped water phantom. The effects of standard (0.1 mmol/kg) and high-dose (0.3 mmol/kg) gadoteridol on spin-echo and SPGR images were also investigated in three patients. RESULTS The measured amplitude of undoped water and the rate of increase of doped water signal with increasing gadopentetate concentration (slope) for spin-echo 600/11/1/90 degrees (repetition time/echo time/excitations/flip angle) and SPGR (600/11/190 degrees) were similar and exceeded those of SPGR (35/5/145 degrees). Greater increases in SPGR doped water signal and its slope were produced by increasing TR than by varying echo-time or flip angle. The subjective lesion conspicuity and measured lesion contrast at 0.3 mmol/kg were greater with spin-echo (600/11/1/90 degrees) than with SPGR (35/5/145 degrees) in all three patients; the measured lesion enhancement was similar for both techniques in two patients and decreased for SPGR in the third patient. CONCLUSIONS The phantom studies suggest that the short repetition time of 35 msec, typically used in clinical SPGR imaging, is largely responsible for a reduced signal amplitude and a diminished rate of increase of signal with increasing gadopentetate concentration, relative to spin-echo. Phantom and clinical studies suggest that the dose of paramagnetic agent required to achieve SPGR lesion conspicuity with short repetition time comparable with spin-echo would have to be higher than the dose in current clinical use.